Cranioplasty after decompressive craniectomy in hemorrhagic moyamoya disease. (December 2019) - Ge, Peicong; Zhang, Qian; Ye, Xun; Liu, Xingju; Deng, Xiaofeng; Wang, Jia; Wang, Rong; Zhang, Yan; Zhang, Dong; Zhao, Jizong
Highlights: The balance between spontaneous postoperative revascularization and the need for cranioplasty is difficult. Spontaneous revascularization after decompressive craniectomy in MMD patients should be evaluated before cranioplasty. Postoperative treatment should be discussed individually based on spontaneous revascularization. Abstract: The objective of this study was to investigate cranioplasty after decompressive craniectomy in hemorrhagic moyamoya disease (MMD). We retrospectively reviewed seven patients with hemorrhagic MMD after decompressive craniectomy from January 1, 2010 to December 31, 2018. Clinical features, radiological findings, and outcomes were analyzed. The study included four females and three males, with a mean age at diagnosis of 38.7 years (range 19–56 years). The mean days between craniectomy and DSA was 255 days (with a range of 92–382 days). Three in seven patients had good spontaneous revascularization, while four patients had poor spontaneous revascularization. For patients with good spontaneous revascularization, the computer-assisted design titanium implants for cranioplasty was cut off on the lower edge of the bone window, and all three patients had no complications after cranioplasty and had relatively stable prognosis. For patients with poor spontaneous revascularization, only two patients received cranioplasty. And one in those had unfavorable outcome because of recurrent hemorrhage. In conclusion, spontaneous revascularization after decompressive craniectomy in MMD patients should be evaluated before cranioplasty, and postoperative treatment should be discussed individually.